INOVASI DALAM PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM: ANALISIS PENGGUNAAN AUDIO VISUAL SEBAGAI MEDIA PEMBELAJARAN - Afiah Syasya Ainaya; Shobah Sofariyani Iryanti (LPPM STAI Muhammadiyah Probolinggo, 2024)
Learning media is a very important factor in supporting the success of the teaching and learning process. Global limitations emphasize the need for the world of education to continue to adapt to technological advances to improve the quality of education, especially in the use of information and communication technology in learning, especially in the subject of Islamic Cultural History there are still problems of student misunderstanding caused by inappropriate learning methods and media. This article is written to explain the role of audio-visual media in improving the learning process and outcomes of Islamic Cultural History. The research method used is library research. The data used is in the form of articles that discuss the use of audio-visual media in learning Islamic Cultural History, the article is systematically reviewed as the main data in research. This research takes sources from articles published in the last 4 years (2020-2024). The data used in this study was collected from various sources, namely: Google Scholar, Sinta, and Publish or Perish The data collection technique used in this study is to search and construct from various sources, such as journals, books, and from several relevant previous studies. The results showed that learning cultural history using audio-visual media is very effective because it can help students to feel the atmosphere of Islamic culture directly through virtual worlds such as documentary videos, historical simulations, and virtual-based applications. This provides a new experience in the learning process